"State ineffectiveness in deterring organized crime style homicide in Mexico: a vicious cycle" - Schatz, Sara (Crime, law and social change, 2021)
Institutional weaknesses in the criminal justice system (limited court capacity and the increasingly sophisticated armament of splintering drug trafficking organizations) limit the effectivity of Mexican states to deter organized crime style homicide. Court capacity, expressed by increasing sentencing rates in states where the oral court system was institutionalized, remains insufficient against the post-2006 organized crime related homicide epidemic. The illegal arms market, combined with long-standing deficits in firepower between organized crime and municipal police forces, limit the state’s capacity to alter the arms balance toward policing forces. Taken together, limited court capacity and the tactical imbalance of weapons held by drug trafficking organizations create a vicious cycle which continually perpetuates state ineffectiveness to deter and punish organized crime style homicide.